The Effectiveness of Puzzle Play Therapy in Reducing Anxiety Due to Hospitalization in Preschool Age Children (3-6 Years) in the Sakura Room at Tenriawaru Bone Regency Hospital - Andi Satriana; Dewi Mulfiyanti; Megawati; Sumarni (International Journal of Public Health Excellence (IJPHE), 2023)
Hospitalization is a planned or emergency process that requires the child to undergo treatment in hospital and undergo a therapy program until he is sent home. Hospitalization of children can cause anxiety and stress at all ages. Anxiety in children can be overcome by channeling feelings of anxiety into a fun play activity, so that it is hoped that it can support the healing process and be cooperative in every nursing action. Puzzle play therapy is one of the play therapies that can be given to preschool-aged children while undergoing hospitalization. Through the activity of playing puzzles, it is hoped that it can provide a feeling of joy and be an effective way to forget about anxiety for children. The aim of implementing evidence-based nursing practice is to overcome anxiety in preschool-aged children during hospitalization. This type of research uses a quasi-experimental method with a one group pretest posttest design. Data were collected using the Hamilton Rating Scale for Anxiety (HAR-S) questionnaire. The sample was determined using purposive sampling with a total of 24 respondents. The statistical results of the paired sample t-test showed ap value of 0.000 (p value < α 0.05) so it can be concluded that There is an effect of puzzle playing therapy on anxiety in hospitalized children. This research suggests puzzle playing therapy to hospitalized children as providing an effective way to reduce anxiety.